Bacterial Vaginosis: What Do We Currently Know? - Abou Chacra, Linda; Fenollar, Florence; Diop, Khoudia (Frontiers in Cellular and Infection Microbiology, 2022)
The vaginal microbiome is a well-defined compartment of the human microbiome. It has unique conditions, characterized by the dominance of one bacterial species, the Lactobacilli. This microbiota manifests itself by a low degree of diversity and by a strong dynamic of change in its composition under the influence of various exogenous and endogenous factors. The increase in diversity may paradoxically be associated with dysbiosis, such as bacterial vaginosis (BV). BV is the result of a disturbance in the vaginal ecosystem; i.e., a sudden replacement of lactobacilli by anaerobic bacteria such as Gardnerella vaginalis, Atopobium vaginae, Ureaplasma urealyticum, Mycoplasma hominis, and others. It is the most common cause of vaginal discharge in women of childbearing age, approximately 30% of all causes. The etiology of this dysbiosis remains unknown, but its health consequences are significant, including obstetrical complications, increased risk of sexually transmitted infections and urogenital infections. Its diagnosis is based on Amsel's clinical criteria and/or a gram stain based on the Nugent score. More recently, a molecular biology tool has been developed: the qPCR, which is considered the "gold standard" of the diagnostic tools for BV. The treatment of bacterial vaginosis aims at restoring the balance of the vaginal flora to stop the proliferation of harmful microorganisms. Prescription of antibiotics such as metronidazole, clindamycin, etc. is recommended. Faced with the considerable uncertainty about the cause of BV, the high rate of recurrence, the unacceptable treatment options, and clinical management which is often insensitive and inconsistent, research on this topic is intensifying. Knowledge of its composition and its associated variations represents the key element in improving the therapeutic management of patients with the most suitable treatments possible.